The Implementation of a Progressive Aproach PBL Model to Improve Students Reading Comprehension at English Study Program FKIP -UR - Erni Erni; Hamidah Yamat (Universitas Negeri Padang, 2014)
Based on the curriculum of English Study Program FKIP University of Riau, Reading as a subject course is focused on reading for academic purposes which required high academically demanding. Data of students post-test in previous semester show that students find difficulties in comprehending academic text. The teaching method applied by lecturers in the reading class did not engage students to learn fully that the result of students reading score could not reach the minimum achievement criteria of Reading III. This research is classroom action research. The objectives of this study were to know how PBL can improve the reading comprehension of the third semester students of English Study Program FKIP University of Riau and to know what factors give dominant increase to the reading comprehension of the third semester students of English Study Program FKIP UR.The result of the study found that PBL Model which is derived from constructivism theory can improve the reading comprehension the third semester students of English study program FKIP UR. The data analysis showed that the mean of pre test is 45.78, post test I is 70.03 and post test II is 75.95. The improvement was due to the increase on students’ activity and motivation well in learning reading by using PBL Model. It was because this model can facilitate students in identifying the problems, brain storming, analyzing, formulating problem, self-study and presenting activities